2023
DOI: 10.3390/molecules28165974
|View full text |Cite
|
Sign up to set email alerts
|

Geoherbalism Metabolomic Analysis of Atractylodes lancea (Thunb.) DC. by LC-Triple TOF-MS/MS and GC-MS

Abstract: The rhizome of Atractylodes lancea (Thunb.) DC. (AL), called Maocangzhu in Chinese, is a geoherbalism medical herb in Jiangsu Province that is often used in the prescription of traditional Chinese medicine (TCM), such as for the treatment of COVID-19. The landform and climatic environment of each province varies greatly from south to north, which has an important influence on the chemical constituents in AL. However, there is a lack of research on the significance of its geoherbalism, especially in water-solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…At present, most of the analysis of TCM prescriptions is devoted to separating and purifying compounds from the formula, and then using mass spectrometry, chromatography methods and some other coupled technologies to determine the mechanism of action between compounds [ [7] , [8] , [9] , [10] ]. However, the composition of TCM is complicated, and the whole process of separation and purification is complicated and laborious.…”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the analysis of TCM prescriptions is devoted to separating and purifying compounds from the formula, and then using mass spectrometry, chromatography methods and some other coupled technologies to determine the mechanism of action between compounds [ [7] , [8] , [9] , [10] ]. However, the composition of TCM is complicated, and the whole process of separation and purification is complicated and laborious.…”
Section: Introductionmentioning
confidence: 99%
“…Modern research has revealed that the volatile oil of Atractylodes lancea primarily composed of sesquiterpenes, possesses notable anticancer, antioxidant, anti-inflammatory, antibacterial, and hepatoprotective effects [ 3 ]. The chemical composition of the volatile oil of Atractylodes lancea is complex, with sesquiterpenes being its main constituents [ 4 ]. ATaAL-EO, drawn from these plants, can be leveraged as natural constituents for the formulation of diverse products like herbal harmonies, traditional Chinese medicine prescriptions, fragrances, food additives, and skin care products [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%